2006
DOI: 10.1158/1535-7163.mct-05-0446
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced epidermal growth factor receptor activation determines response to combined gefitinib/chemotherapy treatment in non–small cell lung cancer cells

Abstract: Activating epidermal growth factor receptor (EGFR) mutations have been linked with sensitivity to gefitinib and erlotinib; however, there are no established predictive markers for response to the combination of EGFR inhibitors with standard chemotherapy in non -small cell lung cancer (NSCLC) patients. In this study, we characterized a panel of human EGFR wild-type and mutant NSCLC cells for their sensitivity to gefitinib alone and in combination with cisplatin or Taxol. Cell viability was assessed using 3-(4,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
59
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 49 publications
13
59
1
Order By: Relevance
“…The H1975 cell line carrying the L858R and T790M mutations was resistant to gefitinib [7]; the H1650 cell line, despite harboring a delE746_A750 activating mutation in the exon 19 of the EGFR gene, was resistant to gefitinib and erlotinib as previously reported [28][29][30]; K-RAS mutations were found in four of the tested resistant cell lines.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The H1975 cell line carrying the L858R and T790M mutations was resistant to gefitinib [7]; the H1650 cell line, despite harboring a delE746_A750 activating mutation in the exon 19 of the EGFR gene, was resistant to gefitinib and erlotinib as previously reported [28][29][30]; K-RAS mutations were found in four of the tested resistant cell lines.…”
Section: Resultssupporting
confidence: 71%
“…The response of sensitive cell lines to gefitinib was previously correlated with dependence on AKT and MAPK activation in response to EGFR signaling [34] and on inhibition of both PI3K/AKT/mTOR and MAPK pathways following gefitinib treatment [28,35,36]. In the three highly sensitive cell lines we observed a marked reduction on p-p44/42 MAPK, on p-AKT, and on p-S6K following gefitinib treatment (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A significant antagonism was observed between gefitinib-and oxaliplatin-induced cell death in cell lines with low basal EGFR phosphorylation levels, whereas in cell lines with high basal EGFR phosphorylation, the interaction between gefitinib and oxaliplatin was additive and often supraadditive/synergistic (Van Schaeybroeck et al, 2005). Similar results were obtained in human NSCLC cells (Van Schaeybroeck et al, 2006). However, different data were obtained for cetuximab preclinical antitumour activity (monotherapy and combination based), which was not predicted by relative total or activated EGFR tumour expression levels (Wild et al, 2006).…”
Section: A Ray Of Hopesupporting
confidence: 75%
“…Recent studies reported EGF can inhibit or stimulate Fas-induced apoptosis [14,20,25], and the EGF receptor (EGFR) is frequently upregulated in response to chemotherapy [11,42]. EGF can also modulate TGFb and/ or Fas/FasL expression and activity [14,40,45].…”
Section: Introductionmentioning
confidence: 99%